Empowering Pre-Service Teachers to Produce Ubiquitous Flipped Classes (2017)
This work focuses on technological and educational outcomes that resulted from the production of foreign language educational videos by 90 pre-service instructors enrolled in an official Master’s Degree in Secondary Education programme. This teaching practice, conducted during two consecutive years, was set in a ubiquitous learning environment with the intention of effectively linking digital technology with pedagogy by means of producing flipped classroom units. The findings reveal that these pre-service teachers successfully combined instructional dynamics with digital skills to produce flipped classes adapted to the young generation’s needs. The classroom becomes, therefore, a more participatory learner-centred scenario with a variety of interactive and collaborative activities performed by foreign language students.